Topical and transdermal drug delivery : principles and practice - Benson, Heather A. E.; Watkinson, Adam C. (Hoboken, N.J. : Wiley, 2011)
'By understanding the mechanisms by which compounds cross the skin, it becomes possible to devise means for improving drug delivery. Providing an overview of the current science in drug and cosmetic application to and through the skin, Topical and Transdermal Drug Delivery includes treatment of skin conditions, skin permeation, and enhancement and measurement of skin permeation. The book provides pharmaceutical scientists, skin product development experts, and those in the cosmetic and personal care industry with practical knowledge and insight into future product development'--Provided by publisher.
Keywords: Administration, Cutaneous; Administration, Topical; Drug delivery systems -- methods; Skin absorption